2018
DOI: 10.1039/c8ra05499a
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of erythromycin and bacitracin antibiotics into natural sporopollenin microcapsules: antibacterial, cytotoxicity,in vitroandin vivorelease studies for enhanced bioavailability

Abstract: Antibacterial activity and bioavailability of antibiotics are enhanced after a successful loading into nontoxic natural Lycopodium clavatum sporopollenin microcapsules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…Interestingly, it was revealed that sporopollenin of Lycopodium clavatum formulated with ovalbumin, a model antigen, stimulated a “systemic and a mucosal immune response” following oral administration to mice [ 76 ]. Required for industrial applications, the biocompatibility and biodegradability of sporopollenin extracted from Lycopodium clavatum have been proven in several studies [ 52 , 53 , 56 , 74 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it was revealed that sporopollenin of Lycopodium clavatum formulated with ovalbumin, a model antigen, stimulated a “systemic and a mucosal immune response” following oral administration to mice [ 76 ]. Required for industrial applications, the biocompatibility and biodegradability of sporopollenin extracted from Lycopodium clavatum have been proven in several studies [ 52 , 53 , 56 , 74 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The drug-filled microcapsules have been found to be effectual for human colon carcinoma cell line via MTT assay [ 40 ]. In another study, the sporopollenin isolated from Lycopodium clavatum spores was utilized for the encapsulation of erythromycin and bacitracin antibiotics [ 41 ]; the entrapment and filling competence of erythromycin were 32.4% and 16.2, respectively. The activities of antibiotic-loaded sporopollenin, pure antibiotics, and unfilled sporopollenin have been evaluated against Pseudomonas aeruginosa , Staphylococcus aureus , and Klebsiella pneumoniae .…”
Section: Drug Delivery Applicationsmentioning
confidence: 99%
“…A deviation from Fick's law was illustrated by the in vitro discharge mechanism for erythromycin at pH 7.4. I The discharge of erythromycin in vivo from sporopollenin (oral dosage 50 mg kg −1 ) showed remarkable values displaying the improved bioavailability of erythromycin [ 41 ].…”
Section: Drug Delivery Applicationsmentioning
confidence: 99%
“…These unique properties have already drawn researchers’ attention [ 2 ]; notwithstanding, it is well known that most pollens contain allergens that constitute a potential risk to human health [ 1 , 9 ]. A few protocols have already been established for the elimination of such components and/or the chemical extraction of sporopollenin from fern spores and pollen grains [ 10 , 11 , 12 ] to encapsulate drugs [ 13 , 14 ], lipids [ 15 ], cells [ 16 ], proteins [ 17 , 18 ], or chemical catalysts [ 19 , 20 ]. Such procedures usually involve laborious processes using harsh reagents (e.g., strong acids and/or bases) and prolonged incubation times that can alter the ultrastructure of the pollen grain [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%